Observation of Hermann’s Tortoise (Testudo hermanni) C Lutching without the Presence of Males and Eggshell Mortality on a Large Tortoise Farm in Slovenia Over a Three-Year Period - Mateja Stvarnik (Sciendo, 2020)
The aim of this study was to determine the percentage of hatched and fertilized eggs in female Hermann’s tortoises before and after the removal of males after breeding.